MYLead: Malaysian Young Leaders - Mohammad Hasif Mohd Tahir (Penerbit Universiti Kebangsaan Malaysia, 2024)
MYLead: Malaysian Young Leaders aims to train students and give them the opportunity to share their knowledge with other students. This programme aims to develop students' talent and courage to work in a team, take instructions, and make quick decisions that are appropriate to life at university and in the working world. This approach can improve and strengthen the mindset of the younger generation, who will be leaders in the future. This programme is considered important because it can strengthen the brotherhood between students who are considered future leaders. The programme targets future leaders, such as high school students, and uses high school students as facilitators to provide information to achieve programme goals. A total of 159 students were distributed across five schools to ensure the success of the program. We received positive feedback from both students and teachers. The programme features fun activities such as ice-breaking and group training based on key leadership skills (TCLC). Students can also get out of their comfort zone to become more courageous and gain leadership skills. This programme can enhance students' understanding of the spirit of collaboration, leadership skills, and the open-mindedness they need as future leaders.